2011
DOI: 10.1089/pho.2010.2783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Treatment with an 80-Hz Pulsed Infrared Diode Laser on Mast-Cell Numbers and Degranulation in a Rat Model of Third-Degree Burn

Abstract: We conclude that LLLT can significantly decrease total numbers of mast cells during the proliferation and remodeling phases of healing in a rat model of third-degree burn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
19
0
7
Order By: Relevance
“…Our results and interpretation are supported by previous evidence in which Assis et al demonstrated that NIR 808 nm laser at a dose of 180 J/cm 2 , 3.8 mW/cm 2 decreases NF-kB expression, which led to reduce TNF-α level in cryolesion of tibialis anterior muscle in rats [35]. In another study, LLLT with 80 Hz pulsed NIR 890 nm laser significantly decreased the total number of the mast cells and degranulation during the proliferation and remodeling phase in third-degree burns in rats [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Our results and interpretation are supported by previous evidence in which Assis et al demonstrated that NIR 808 nm laser at a dose of 180 J/cm 2 , 3.8 mW/cm 2 decreases NF-kB expression, which led to reduce TNF-α level in cryolesion of tibialis anterior muscle in rats [35]. In another study, LLLT with 80 Hz pulsed NIR 890 nm laser significantly decreased the total number of the mast cells and degranulation during the proliferation and remodeling phase in third-degree burns in rats [10]. …”
Section: Discussionmentioning
confidence: 99%
“…In burn injury, the entire epidermis and most of the dermis are affected which produces a hypertrophic scar and inflexibility which leads to serious cosmetic problems with consequences in haemostasis, inflammation process, reepithelialisation and extracellular matrix remodelling [1]. As consequence, there is increasing interest in therapies that accelerate the healing of burn injuries, increase the quality of the scar and reduce the treatment cost [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, low-level laser therapy (LLLT) has been used for the treatment of burn injuries [1,3,[15][16][17][18][19]. Knowledge of the depth penetration of laser radiation in tissue is an essential prerequisite for identifying its method of action [20].…”
Section: Introductionmentioning
confidence: 99%
“…On day 13, there were significantly lower numbers of types I and II mast cells at the laser-treated burn sites compared with the other burn sites. Khoshvaghti et al [38] concluded that LLLT significantly declined total numbers of mast cells through the proliferation and remodeling phases of healing in a rat model of third-degree burn. Ezzati et al investigated the influence of PW LLLT on healing of a deep second-degree burn model in rats.…”
Section: Skin Burn Healingmentioning
confidence: 99%